ANALISIS PREDIKTIF KEMAMPUAN DASAR MATEMATIKA TERHADAP HASIL BELAJAR STATISTIKA MAHASISWA - Muhammad Zainudin Sani; Sedya Santosa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The aim of this research is to obtain data and information about the influence of basic mathematics skills on the statistics learning outcomes of Physics Education students in the Basic Statistics course. Students who have low basic mathematics skills tend to have difficulty understanding any material taught in courses that require algebraic analysis and calculations. The population of this research is third semester students of the Department of Physics Education, Faculty of Teacher Training and Education for the 2024/2025 academic year. This type of research is experimental research. The data collection method in this research was taken through basic mathematics ability tests and student statistics learning outcomes tests. The data obtained was analyzed using regression analysis. From the results of this research, it was concluded that (1) 32.95% of basic mathematics abilities explain the basic statistics learning outcomes of students in the Department of Physics Education and the remaining 67.05% is explained by other independent variables; (2) basic mathematics abilities influence the basic statistics learning outcomes of students in the Department of Physics Education and (3) basic mathematics abilities have a positive influence on the basic statistics learning outcomes of students in the Physics Education Department, with the regression equation (Y ) = 54.86 + 0.348 X. This means that a student's final grade in the Basic Statistics Course is influenced by the level of basic mathematical abilities possessed by the student.